THE EFFECT OF FINANCIAL INCLUSION AND BANKING BEHAVIOR ON HOUSEHOLD DEBT BEHAVIOR - HERISPON HERISPON (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This study aims to examine the effect of financial inclusion from the dimensions of access, user, quality, wealth on bank behavior and debt behavior and the indirect influence of each dimension of financial inclusion on bank behavior and household debt behavior. With population areas and samples in the city of Pekanbaru, Riau, Indonesia.The research focused on the demand side in banking services, namely consumer credit services to households. Using a purposive sampling method with a total sample of 303 household units in the city of Pekanbaru.The analysis tool used in the study was SEM-WarpPLS version 6.From this study the authors found that access, user, quality, wealth had a positive effect on the behavior of household debt, then the authors found that access, user, quality had a positive effect on bank behavior, then found that access, user, quality, wealth had an indirect positive effect towards debt behavior through mediating bank behavior.It was concluded from this study that the behavior of banks as mediating variables can reduce the direct influence of financial inclusion on the behavior of household debt.